Beyond honour: a historical materialist explanation of honour related violence - Khan, Tahira S. (Oxford Univ. Press, 2006)
"Beyond Honour" addresses the issue of honour related violence by using Marx's Historical Materialist approach. This study is a blend of academic research and personal experiences. It is an attempt to look beyond the cultural notion of honour as the main/only motive behind gender-based violence by examining related issues through historical academic research along with the simple narration of present day stories of victims around the globe.